Impact of walking speed and slope of the ground on axial force of poles in Nordic walking - Martin Pšurný; Miroslav Janura; Jakub Krejčí; Aleš Jakubec (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
BACKGROUND: Nordic walking (NW), due to its attractiveness and convenience of equipment, is becoming more popular and utilised in the areas of sports, recreation and physiotherapy. Some of its impacts on load to the body have not yet been sufficiently explored. OBJECTIVE: The objective of the study was to determine the impact of walking speed and slope of the ground on the magnitude of axial forces, transferred to the poles by upper extremities during NW. METHODS: The study was participated in by 17 healthy subjects, aged 25.9 ± 3.6 years, who went through 12 independent measurements on a treadmill in various speeds (6.0; 6.6; 7.2 and 7.8 km • h–1) and slopes (0; 5 and 7.5%). These measurements provided us with values of basic spatiotemporal variables, characterizing NW performance and force variables, acting on the poles. RESULTS: Increased walking speed led to increase in cycle frequency (p < .001) and increase in peak poling force and average poling force (p < .001). Poling time reduced with increasing speed (p < .001). Increase in slope of ground had no significant impact on the magnitude of time and dynamic variables. CONCLUSIONS: Increased walking speed during NW increases the force, generated by the upper extremities on the poles. During NW it is possible to prefer walking speed rather than to change the slope of the ground for those patients, who are indicated to strengthen upper extremities.